Evaluating The PRRI Rebellion As A West Sumatran Peasant Movement - Fogg, Kevin W. (Fakultas Ilmu Sosial Universitas Negeri Padang, 2015)
This paper examines the following questions: Had the peasants understood the vision of the leadership, would they still have participated in the revolt? Was the swift reluctance towards active military participation the result of a better understanding of the rebellion’s aims as espoused by the core leadership? Are the Minangkabau peasantry prone to future profanations of great tradition narratives? By way of using various sources, the writer tries to trace the PRRI Rebellion in the light of grass-root perspective as it is reflected in the eye of interviewee given Om Fahmi’s description, that believed that the Minang will continue to protest against the imperialism of Jakarta until this state of affairs appeared.Keywords: PRRI rebellion, peasant movement, revolt